2021
DOI: 10.22266/ijies2021.0831.31
|View full text |Cite
|
Sign up to set email alerts
|

Modified Focal Loss in Imbalanced XGBoost for Credit Card Fraud Detection

Abstract: The development of credit card use in Indonesia has not been matched by the security provided by credit card service providers. This resulted in significant losses both in terms of banking and customers. The difficulty in finding the characteristics of credit card fraud is one of the biggest challenges. Currently, many are developing machine learning models that can identify credit card fraud to help banks. Unfortunately, the model created is mostly biased towards the class which has more dominant data. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, the study recommends adopting the suggested model by using massive dataset instead of using sampling technique. In addition, some articles such as Trisanto et al (2021) and Singh, Ranjan & Tiwari (2021) applied undersampling techniques and oversampling techniques.…”
Section: Results and Analysismentioning
confidence: 99%
“…However, the study recommends adopting the suggested model by using massive dataset instead of using sampling technique. In addition, some articles such as Trisanto et al (2021) and Singh, Ranjan & Tiwari (2021) applied undersampling techniques and oversampling techniques.…”
Section: Results and Analysismentioning
confidence: 99%
“…For instance, F. Wan [14] proposed a supply chain fraud detection model based on XGBoost and random forest hybrid to detect fraud in DataCo intelligent supply chain dataset. C. Meng [15] evaluated the performance of the XGBoost algorithm on the original credit fraud dataset, undersampling, and SMOTE datasets separately; D. Trisanto [16] introduced an enhanced focal loss technique (W-CEL loss unbalanced parameter) for unbalanced XGBoost. This research aimed to refine the focus weight loss, indicating that the method could only yield effective and unbiased machine learning models with mildly unbalanced data.…”
Section: Ensemble Tree Methodsmentioning
confidence: 99%
“…Because independent variables are harder to comprehend in feature selection, the system is more likely to lose information as a result. To enhance the ability of focal loss and provide weight to the class that is often misunderstood, Trisanto [22] presented modified Focal loss for imbalance XGBoost. Using data on credit card fraud, the modified focal loss approach is assessed and contrasted with the standard method.…”
Section: Literature Reviewmentioning
confidence: 99%